Yaroslav Sokolov and his School - V. Ya. Sokolov; A. L. Dmitriev (Учёт. Анализ. Аудит, 2023)
The article is devoted to the 85th anniversary of the outstanding scientist in the field of accounting, doctor of economic sciences, honored worker of science of Russian Federation, professor Yaroslav Vyacheslavovich Sokolov (1938–2010). The authors made an attempt to review the multifaceted scientific and pedagogical activities of the scientist over nearly 50 years. The authors analyze Sokolov’s ideas in the field of accounting, as well as his contribution to the creation of certain areas (the Sokolov school); his works in the field of history, which won him universal recognition, among which a special place is given to his republished work «Treatise on Accounts and Records» by Luca Pacioli; the social and educational activities of the scientist on the background of changing economy in the country and in the world are shown. An attempt has been made to assess comprehensively the role of Professor Sokolov in the formation of the process of training specialists in accounting, analysis and audit, as well as statistics.